Regulating the global information society - Marsden, Christopher T. (London ; New York : Routledge, 2000)
An outstanding line-up of contributors explore the regulation of the internet from an interdisciplinary perspective. In-depth coverage of this controversial area such as international political economy, law, politics, economics, sociology and internet regulation. Regulating the Global Information Society covers the differences between both US and UK approaches to regulation and establishes where policy is being made that will influence the future direction of the global information society, from commercial, democratic and middle-ground perspectives.
Introduction : information and communications technologies, globalisation and regulation / Christopher T. Marsden -- Part I. Theoretical perspectives. The role of the public sphere in the information society / Nicholas Garnham -- In search of the self : charting the course of self-regulation on the internet in a global environment / Monroe E. Price and Stefaan G. Verhulst -- Will electronic commerce change the law? Towards a regulatory perspective based on competition, information and learning skills / Paul Nihoul -- Part II. The limits of telecommunications regulation. How far can deregulation of telecommunications go? / Martin Cave -- Realising social goals in connectivity and content : the challenge of convergence / Richard Collins -- Commentary : when to regulate in the GIS? A public policy perspective / Fod Barnes -- The rise and decline of the international telecommunications regime / William J. Drake -- After Seattle : trade negotiations and the new economy / Jonathan D. Aronson ; Comment / Dimitri Ypsilanti -- Part III. International self-regulation and standard setting. Locating internet governance : lessons from the standards process / Mark Gould -- Semi-private international rulemaking : lessons learned from the WIPO domain name process / A. Michael Froomkin -- Part IV. Standard setting and competition policy. Will the internet remake antitrust law? / Mark Lemley -- The problems of the third way : a Java case study / David McGowan -- Part V. The limits of government regulation. China's impact on the Global Information Society / Perry Keller -- Freedom versus access rights in a European context / Ad van Loon -- Pluralism, guidance and the new media / Thomas Gibbons -- Five challenges for regulating the Global Information Society / Pamela Samuelson.
Includes bibliographical references (pages 331-357) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Computer networks -- Law and legislation; Telecommunication -- Law and legislation; Digital communications; Information society; Réseaux d'ordinateurs -- Droit; Télécommunications -- Droit; Transmission numérique.; Société de l'information.; LAW -- Media & the Law; LAW -- Communications; Computer networks -- Law and legislation; Digital communications; Information society; Telecommunication -- Law and legislation